Charakterystyka hydrogeochemiczna wód eksploatowanych w Uzdrowisku Szczawnica - Michalski, Andrzej (My University, 2012)
Therapeutic waters from Szczawnica have been known from sixteenth century. In the “Szczawnica ?” mining area, Szczawnica Spa is exploiting therapeutic waters from 10 groundwater intakes. These groundwaters have specific chemical composition which depend on many factors. The paper describes hydrogeochemical conditions of therapeutic waters and fresh waters. Chemical conditions of these groundwaters are described by temporal variability of selected minerals, Stiff’s and Piper’s diagrams, maps of changes chemical parameters, map of hydrogeochemical conditions and modeling calculations. Analyzed groundwaters are mostly chloride, CO2–rich waters with bromide and iodide.

Wody lecznicze w Szczawnicy są wzmiankowane od XVI wieku. Na utworzonym obszarze górniczym i terenie górniczym „Szczawnica I” Uzdrowisko Szczawnica prowadzi eksploatację wód leczniczych z 10 ujęć. Wody te są specyficzne pod względem składu chemicznego, na ich wyjątkowość wpływa szereg uwarunkowań. W niniejszej pracy scharakteryzowano warunki hydrogeochemiczne wód leczniczych i wód zwykłych z obszarów zasilania. Charakterystykę chemizmu wód przedstawiono w postaci zmian czasowych wybranych składników, diagramów Stiffa i Pipera, map rozkładu wybranych parametrów, mapy hydrogeochemicznej oraz obliczeń modelowych. Analizowane wody to głownie szczawy chlorkowe z składnikami swoistymi Br- i ?.
Characteristic of hydrogeochemical conditions of groundwaters exploited in Szczawnica Spa
Keywords: Szczawnica Spa; Uzdrowisko Szczawnica; therapeutic waters; wody lecznicze; hydrogeochemical modelling; modelowanie hydrogeochemiczne